Government Integration Policy In Crime Prevention: Sexual Violence Against Children In Indonesia - Adnan, Idul (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This research aims to analyze policy models for the government to prevent sexual violence against children, identify obstacles faced in its implementation, and formulate a more ideal integrative research policy model. This is research normative with a socio-legal research approach, namely analyzing normative law with an understanding of the social context and the dynamics of society. The research data, namely primary data, regulations, relevant legislation, and secondary data, were obtained from books, journals, and a report study. This research discloses that the Indonesian government has implemented several policies to handle cases of sexual violence against children. Policies that cover regulatory law, such as the Child Protection Act and the sexual violence crime act, prevention programs like child-friendly schools, as well as the provision of protective services for the victims. The implementation still faces challenges, such as a lack of coordination between institutions, limited source power, human and infrastructure, and low societal awareness, resulting in a lack of reported cases. To overcome obstacles, a more integrative and practical policy model is needed, including strengthening coordination between agencies to form a unit task special, improving source power and infrastructure, such as the regional technical implementation unit for the protection of women and children, as well as implementing more firm and restorative measures. In addition, public awareness needs to be improved through education and the public, as well as the utilization of technology in system reporting, based on big data analysis for supporting prevention, as well as handling cases of sexual violence against children more optimally.